Synthesis and Characterization of Lanthanide(III) Complexes with 2,4-pyrimidine diamine-5[(3,4,5-trimethoxy phenyl) methyl] - V. Lokhande, Manohar (Asian Journal of Chemistry, 2010)
Complexes of La3+, Pr3+, Nd3+, Sm3+, Gd3+, Tb3+ and Dy3+ with 2,4-pyrimidine diamine- 5[(3,4,5-trimethoxy phenyl) methyl] have been prepared. The structures of the complexes have been established on the basis of elemental analysis, magnetic moment, infrared, thermal analysis, X-ray powder diffraction and electronic spectra. The complexes are active towards gram-positive bacteria. The ligand is bonded through nitrogen and slight participation with 4f electron in bond formation.